Application of nanomaterials in tumor radio-sensitization - Zhong , Yiyi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Cancer is a main reason of death worldwide, there was about 10million deaths caused by cancer in 2020. Radiotherapy, as a traditional method of treating cancer, uses radiation to kill the lesions of tumor patients. People develop radiation sensitizers to improve the treatment efficiency of radiotherapy and achieve better therapeutic effects through multiple collaborative treatments. Because nanomaterials have special physical and chemical properties, they may bring us novel methods to increase the effectiveness of treatment and reduces damage to the patient’s body. People construct nanoplatforms loaded with multiple drugs to achieve a combination of radiation sensitization, toxicity reduction, and biocompatibility enhancement. At present, most nano radiation sensitizers are still in the development stage and have not been put into clinical use. The current research provides potential application prospects, but the existence of toxicity or other side effects cannot be ruled out, and the cost is also a problem that these drugs face before clinical use. This article mainly summarizes some methods of nanomaterial enhanced radiation therapy, research achievements in the past five years, and prospects for future development in this field.